2019
DOI: 10.1136/bmjpo-2019-000572
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilisation in children with SMA type 1 treated with nusinersen: a single centre retrospective review

Abstract: BackgroundNusinersen has been used to treat spinal muscular atrophy type 1 (SMA1) in the UK since 2017. While initial trials showed neuromuscular benefit from treating SMA1, there is little information on the respiratory effects of nusinersen. We aimed to look at the respiratory care, hospital utilisation and associated costs in newly treated SMA1.MethodsWe reviewed the medical records of all children within the West Midlands with SMA1 treated with nusinersen at Royal Stoke University Hospital. Baseline demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The publications comprised data from 14 countries, including the USA (n = 20) [48-50, 53, 54, 56, 57, 60, 63, 70, 74, 77, 80, 84-86, 88, 91-93], UK (n = 5) [52,68,81,89,98], Italy (n = 2) [59,83], Australia (n = 2) [64,71], Canada (n = 1) [75], Germany (n = 1) [55], Croatia (n = 1) [87], Korea (n = 1) [65], Japan (n = 1) [66], France (n = 1) [79], Spain (n = 4) [58,72,73,78], Sweden (n = 1) [61], Russia (n = 2) [94,97] and Turkey (n = 1) [96]. Seven studies reported multi-national data [62,67,69,76,82,90,95].…”
Section: Description Of Identified Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The publications comprised data from 14 countries, including the USA (n = 20) [48-50, 53, 54, 56, 57, 60, 63, 70, 74, 77, 80, 84-86, 88, 91-93], UK (n = 5) [52,68,81,89,98], Italy (n = 2) [59,83], Australia (n = 2) [64,71], Canada (n = 1) [75], Germany (n = 1) [55], Croatia (n = 1) [87], Korea (n = 1) [65], Japan (n = 1) [66], France (n = 1) [79], Spain (n = 4) [58,72,73,78], Sweden (n = 1) [61], Russia (n = 2) [94,97] and Turkey (n = 1) [96]. Seven studies reported multi-national data [62,67,69,76,82,90,95].…”
Section: Description Of Identified Studiesmentioning
confidence: 99%
“…b Covering 49 unique studies; two full publications and two conference abstracts were linked studies; both have been retained in the current report as they each report unique relevant data. EBM evidence-based medicine reviews, SLR systematic literature review frequently reported separately for individuals with Type 1 (n = 11) [48,54,57,63,65,66,68,81,84,91,93]; Types 1-3 SMA (n = 11; each type reported separately [52,55,58,59,67,69,71,75,76,96,98]; Type 3 SMA including subgroups (n = 1) [82]; and adult patients with SMA (n = 1) [74] or were reported for a mixed population of individuals with SMA: infantile-onset and other SMA (excluding Type 4 SMA; n = 1) [79]; infantile-onset (≤ 7 years) and later-onset (2-12 years) SMA (n = 1) [61]; Type 1 SMA and other SMA (including Type 4 SMA; n = 2) [50,97]; early-onset SMA (patients with Types 1, 2 and 3 SMA aged ≤ 3 years); and other SMA (later-onset Types 2 and 3 SMA in addition to Type 4 SMA) [n = 1] [60]-reported separately for infantile-onset, childhood-onset and juvenile-onset SMA (n = 1) [70]; reported separately for patients with infantile-onset, childhood-onset and late-onset SMA (n = 1) [77]; a mixed population with Types 1, 2 and 3 SMA (n = 1) [95]; a mixed population with Types 2 and 3 SMA (n = 1) [64]; a mixed population with Types 2 and 3 SMA including subgroups (n = 1) [62]; a mixed population with Types 2 and 3 and unreported SMA type (n = 1) [88]; a mixed population with Types 1, 2, 3 and 4 SMA (n = 1) [73]; and a mixed population with SMA in whi...…”
Section: Description Of Identified Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…SMA patients with more than two copies of SMN2, as a result of duplication, tend to have less severe forms of the disease. Recently, therapeutic breakthroughs, genereplacement therapy using viral delivery [3] and altering SMN2 splicing using antisense oligonucleotides [4], have remarkably improved motor function and survival of SMA patients, but patients remain prone to cardiopulmonary complications leading to opportunistic upper respiratory tract infections [5].…”
Section: Introductionmentioning
confidence: 99%